A CHECK-LIST OF FOSSIL CHONDRICHTHYES FROM BRIELAS (LANGHIAN, PORTUGAL) - Fialho, Pedro (2018)
Located in a slope of the Costa de Caparica motorway, in the peninsula of Setúbal, West Portugal, the outcrop of Brielas stand out as one of the best Miocene sections of the Lower Tagus Basin to collect a great diversity of fossil Chondrichthyes, which are cartilaginous fishes also known as selachians. The first mention regarding this outcrop was made by Antunes and Jonet (1970), in a study focused on the characterization of Serravalian to Tortonian shark fossil forms of Lisbon. The sediments present in Brielas can be correlated with the geological units Vc, VIa and VIIa traditionally used for the Miocene of Lisbon (Cotter in Dollfus et al., 1903-1904). The samples studied were taken from the unit Vc, with approximately four meters thick and characterized by sandy-silt banks, intercalated with fossiliferous biocalcarenites. Through 87Sr/86Sr dating (H. Elderfield) of a Pectinid shell it was determined that the Vc unit has an age of approximately 14 ± 0,4Ma (Antunes et al., 1999), and integrates the depositional sequence S1 (Antunes et al., 2000). The planktonic foraminifera association found by Legoinha (2001) portrays the unit Vc as part of the biozone N9, correlative of the Langhian. The present study aims to contribute to the improvement of the knowledge about Brielas section and its rich marine selachian fauna